Urdu ka guldasta Sooraj mukhi - Fauzia Ehsan Farooqi (Karachi Oxford university Press, 2022)
Urdu Ka Guldasta Sooraj Mukhi is a comprehensive Urdu language textbook aimed at developing students' proficiency in reading, writing, and comprehension. It features a carefully selected collection of prose, poetry, and stories that reflect both classical and modern Urdu literature. The book is designed to enhance grammar, vocabulary, and creative expression, while encouraging students to think critically and engage deeply with the material. Through various exercises and activities, students gain a deeper appreciation for the richness of the Urdu language and its cultural significance, making it a valuable resource for building a strong linguistic foundation.